Factors associated with demand for treated water: A systematic review - Dapari, Rahmat; Mansor, Zawiah; Zainol, Wan Muhd; Alias, Haziq; Zamri, Nurfarhana; Dzulkfli, Nadila; Rusdi, Mardhiyah; Che Dom, Nazri; Hassan, Mohd Rohaizat; Syed Abdul Rahim, Syed Sharizman (Malaysian Journal of Public Health Medicine Association, 2024)
Water demand can be classified into domestic demand and non-domestic demand. Globally, water demand modelling for forecasting and projection has become a popular subject for study in recent years. Studies of water demand aid the water utilities agency and municipal planning in guaranteeing financial, socioecological, and social sustainability. This systematic review aims to present and systematically determine the factors associated with the demand for treated water. Articles related to factors associated with demand for treated water were collected electronically from two different databases, namely Ebscohost (116) and Scopus (250). Two pairs of independent reviewers screened the titles and abstracts of the collected data, stored in Microsoft Excel, against the inclusion and exclusion criteria. Afterwards, the included articles were critically appraised to assess the quality of the studies using the Mixed Method Appraisal Tool (MMAT). Of the 366 articles identified, nine were included in the final review. The demand of treated water is affected by (i) Socioeconomic factors, (ii) Structural factors, (iii) Water supply factors, and (iv) Climate/Geographical factors. The supply of treated water is becoming increasingly limited, due to variuos issues. Therefore, understanding the factors influencing the demand for treated water is critical. The findings from all the related studies may be utilized to improve the implementation of treated water solution programmes, which would help to maximize the successful implementation of demand for treated water programmes.